ASXL genes and RUNX1: an intimate connection? - Metzeler, Klaus H. (American Society of Hematology, 2014)
In this issue of Blood, Micol et al report the discovery of mutations in the additional sex combs-like 2 (ASXL2) gene in about one-quarter of acute myeloid leukemia (AML) patients carrying the t(8;21) translocation.(1)